Peritoneal catheter infections : data from the French language peritoneal dialysis registry (RDPLF), risk factors - Isabelle Vernier; Emmanuel Fabre; Max Dratwa; Christian Verger (RDPLF, 2019)
Peritoneal catheter infections : data from the French language peritoneal dialysis registry (RDPLF), risk factors The French Language Peritoneal Dialysis Registry (RDPLF) record since 1997 all data dealing with peritoneal catheter insertion and follow up. The aim of this study is to analyze catheter infections on 10801 catheters in 144 centres from January 1, 1997 and December 31, 2018. Infections are more common in the first month and 50% occur before the tenth month. The risk of infection increases in case of wall hematoma, initial fluid leakage, and obesity. It decreases with the use of prophylactic antibiotics at the time of catheter insertion, with experienced operator, if the first dressing is delayed for 7 days, and with mupirocin as exit-site prophylaxis. During last two decades the percentage of Staphylococcus aureus infections has decreased, whereas the proportion of Pseudomonas, Corynebacterium and other Gram + cocci increased. The incidence of catheter infections is low compared to literature data: it decreased to 0.16 episodes per year for the 2013-2017 period. Adherence to ISPD guidelines: preoperative antibioprophylaxis is the most followed guideline (70.7% of catheter implantations in 2018). Local antibioprophylaxis concerns only 15.6% of catheters, and remains concentrated in a few centres ; mupirocin is the most frequently used agent. Screening for nasal carriage of S. aureus is performed in only 42% of cases. The catheter section of the RDPLF has allowed the follow-up of clinical practices incidence of infections and ecology for 21 years, both at the national and center level Our study confirms a wide variability in clinical practices, compared to ISPD guidelines.